Remote Learning for Nursing Education in Indonesia during The Covid-19 Pandemic: Efforts and Recommendations - Haryanti, Fitri; Nuraini, Tuti; Sukartini, Tintin; Hidayati, Wahyu; Nursalam, Nursalam; Arofiati, Fitri; Purwati, Nyimas Heny; Nursanti, Irna; Prabawati, Dewi; Trisyani, Yanny; Hadi, Muhammad (Fakultas Ilmu-ilmu Kesehatan, 2022)
The COVID-19 pandemic had an impact on nursing students’ academic and clinical performance. Nursing institutions have provided remote learning to continue the learning process. However, students have met several obstacles that caused a decrease in the quality of learning. Remote learning for education requires the support of information and communication technology. However, studies related to how the COVID-19 pandemic affected nursing education in Indonesia are still rarely done. Accordingly, this study was conducted to evaluate the implementation of remote learning for nursing education during the COVID-19 pandemic. A cross-sectional study was conducted with 331 members of the Association of Indonesian Nurse Education Center (AINEC). The instrument used was the Guidelines of Filling Out Remote Learning. The results showed that 51% of the study programs implemented remote learning, while 69% of the regulations for remote learning were created by rectors. The most common teaching materials were visual, text, and audio-visual content. These materials were distributed through WhatsApp Group, Learning Management System (LMS), and video conference. To support the process of remote learning, nursing institutions need to improve information technology staff and cooperate agreement with other institutions. Overall, the remote learning process needs to be further improved to increase the students’ learning quality.